Ab Initio Entropy Calculations of Water Predict the Interiors of Uranus and Neptune to Be 15%–30% Colder than Previous Models - Burkhard Militzer (The Astrophysical Journal)
Ab initio free energy calculations are employed to derive the entropy of liquid and superionic water over a wide range of conditions in the interiors of Uranus and Neptune. The resulting adiabats are much shallower in pressure–temperature space than those adopted for earlier models of Uranus and Neptune. Our models for their interiors are thus much colder, increasing the likelihood that diamond rain or the recently predicted phase separation of planetary ices has occurred in the mantles of ice giant planets. Based on our ab initio data, we construct interior models for Uranus and Neptune with the concentric MacLaurin spheroid method that match the existing gravity measurements. We compare fully convective models with models that include a convective boundary between liquid and superionic water. We also share a code to characterize giant planet atmospheres where para- and ortho-hydrogen as well as helium are present.